Needs Analysis of the Important Communicative Features at De La Salle University - Siregar, Fenty L. (Lingua Cultura, 2008)
Article analyzed the needs of communicative competence and gather information on the features of communicative competence that are believed to be important by selected foreign graduate students studying at DLSU. The features consist of linguistic, sociolinguistic, discourse, strategic, and intercultural competences. Data were obtained by giving questionnaire to 33 foreign students, consisting of 11 male and 22 females and were analyzed qualitatively. The findings suggest that all features of communicative competence are crucial. In addition, the linguistic competence and strategic competence are considered to be the most essential features of the communicative competence. It can be concluded that the foreign graduate students learn English to achieve their communicative competence and it is used to communicate among students.